Detection of Antimicrobial Resistance Genes Associated with Carbapenem Resistance from the Whole-Genome Sequence of Acinetobacter baumannii Isolates from Malaysia - Mohan Rao; Fairuz A. Rashid; Surianti Shukor; Rohaidah Hashim; Norazah Ahmad (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. The spread of carbapenem-resistant A. baumannii (CrAb) is gaining worldwide attention. The spread of this pathogen is largely due to its ability to acquire various resistance genes of intrinsic and extrinsic origins that confer unpredictable susceptibility to β-lactams. The aim of this study was to analyze β-lactamase genetic compositions of CrAb in Malaysia. Methods. Whole-genome sequencing (WGS) was carried out on 13 CrAb isolates from clinical samples in Malaysia from 2011 to 2016. Results. Endotracheal aspirate was the dominant clinical sample source (n = 6), and only one isolate was obtained from wound swab. A total of 6 sequence types (STs) of the Oxford scheme were identified, including 4 reported STs and 2 novel STs. Eleven isolates were classified into clonal complex 92 (CC92/ICII), among which ST195 and ST208 were the most prevalent STs. All 13 CrAb isolates harbored multiple β-lactamase genes. blaOXA-23 (n = 13) and blaOXA-66 (n = 11) were the dominant carbapenemase gene families found in these isolates. All isolates harbor blaADC, blaOXA-51-like, and blaOXA-23-like genes. blaTEM (n = 7), blaNDM-1 (n = 3), blaCARB-8 (n = 1), and blaPER-3 (n = 1) are amongst other β-lactamase genes found in this study. ISAba1 was found upstream to blaOXA-23 (n = 13), blaOXA-66 (n = 1), and blaADC (n = 11). All blaNDM-1 isolates had ISAba125 (mobile genetic element) upstream to the genes. All isolates were positive for Tn2006/2008 and Tn2009 but were negative for Tn2007. Conclusion. Most of the isolates were grouped under the CC92 clonal complex which belongs to international clonal lineage 2. These findings predict that carriage of carbapenem-resistant genes possibly constitutes the underlying basis of high level of international clone II prevalence. Therefore, molecular surveillance and antimicrobial stewardship are essential in implementing policies to prevent and control the spread of CrAb in hospital settings.